2014
DOI: 10.1007/s11852-014-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of beach rehabilitation success, Turners Beach, Tasmania

Abstract: Beaches worldwide have been subjected to human impacts by the trampling of vegetation, leading to exposure that increases their vulnerability to erosion. Rehabilitation efforts have included dune revegetation and control of human, access along with information signs for public education. Long term evaluation of the success of these is largely lacking, particularly in Australia where there has been significant Natural Resource Management funding in the last 20 years. This study used beach monitoring profiles, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…nourishment) to dunes and beaches (Achab, Ferreira, & Dias, 2014;Matias, Ferreira, Mendes, Dias, & Vila-Concejo, 2005), the construction of sand ridges with and without hard cores (Do Carmo, Reis, & Freitas, 2009;Kratzmann & Hapke, 2012;Wamsley, Waters, & King, 2011), and the facilitation of sand accumulation using fences, vegetation and by managing pedestrian access (Anthony, Vanhee, & Ruz, 2007;Johnston & Ellison, 2014;Lin, 1996;Miller, Thetford, & Yager, 2001; Table S3). nourishment) to dunes and beaches (Achab, Ferreira, & Dias, 2014;Matias, Ferreira, Mendes, Dias, & Vila-Concejo, 2005), the construction of sand ridges with and without hard cores (Do Carmo, Reis, & Freitas, 2009;Kratzmann & Hapke, 2012;Wamsley, Waters, & King, 2011), and the facilitation of sand accumulation using fences, vegetation and by managing pedestrian access (Anthony, Vanhee, & Ruz, 2007;Johnston & Ellison, 2014;Lin, 1996;Miller, Thetford, & Yager, 2001; Table S3).…”
Section: Shoreline Responsementioning
confidence: 99%
See 1 more Smart Citation
“…nourishment) to dunes and beaches (Achab, Ferreira, & Dias, 2014;Matias, Ferreira, Mendes, Dias, & Vila-Concejo, 2005), the construction of sand ridges with and without hard cores (Do Carmo, Reis, & Freitas, 2009;Kratzmann & Hapke, 2012;Wamsley, Waters, & King, 2011), and the facilitation of sand accumulation using fences, vegetation and by managing pedestrian access (Anthony, Vanhee, & Ruz, 2007;Johnston & Ellison, 2014;Lin, 1996;Miller, Thetford, & Yager, 2001; Table S3). nourishment) to dunes and beaches (Achab, Ferreira, & Dias, 2014;Matias, Ferreira, Mendes, Dias, & Vila-Concejo, 2005), the construction of sand ridges with and without hard cores (Do Carmo, Reis, & Freitas, 2009;Kratzmann & Hapke, 2012;Wamsley, Waters, & King, 2011), and the facilitation of sand accumulation using fences, vegetation and by managing pedestrian access (Anthony, Vanhee, & Ruz, 2007;Johnston & Ellison, 2014;Lin, 1996;Miller, Thetford, & Yager, 2001; Table S3).…”
Section: Shoreline Responsementioning
confidence: 99%
“…Dune restoration for defence takes many forms including the direct addition of sand (i.e. nourishment) to dunes and beaches (Achab, Ferreira, & Dias, 2014;Matias, Ferreira, Mendes, Dias, & Vila-Concejo, 2005), the construction of sand ridges with and without hard cores (Do Carmo, Reis, & Freitas, 2009;Kratzmann & Hapke, 2012;Wamsley, Waters, & King, 2011), and the facilitation of sand accumulation using fences, vegetation and by managing pedestrian access (Anthony, Vanhee, & Ruz, 2007;Johnston & Ellison, 2014;Lin, 1996;Miller, Thetford, & Yager, 2001; Table S3). Utilizing multiple techniques within a site, for example beach renourishment in combination with sand fences, to build dunes is common (Bocamazo, Grosskopf, & Buonuiato, 2011;Khalil & Lee, 2006).…”
Section: Shoreline Responsementioning
confidence: 99%
“…The increasing rise of seas levels as a predominant result of global warming combined with excessive coastal development in most small island states has affected widespread erosion that adversely impacts tourist facilities, settlements, and infrastructure (Nurse et al, 2014). Currently, up to 70 % of all beaches worldwide are experiencing some erosion, and this is expected to further increase with the global rise of sea levels (Johnston and Ellison, 2014). This projected loss of beaches may result in severe economic impacts, as any degradation of the beach environment is likely to reduce the 7 demand for coastal tourism and real estate, and directly as well as indirectly affect the income of beach-adjacent businesses and residents.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In a survey of more than 300 tourists visiting the Caribbean island of Barbados, it was found that more than 80 % of tourists would be unwilling to return for the same holiday price if beach areas were reduced (Uyarra et al, 2005). 3 Recognizing the economic importance of maintaining shorelines and beaches in order to protect the livelihood of most local inhabitants, SIDS and other countries facing the issue of coastal degradation have taken measures to protect and rehabilitate shorelines, where topographic evaluations have shown that beach areas can successfully be rehabilitated in this way (Johnston and Ellison, 2014). However, despite the investment of large government funds in rehabilitation efforts, long-term evaluations of program impact are largely lacking in the literature and generally limited to the use of ex-ante cost-benefit analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation